Effect of Lactobacillus plantarum Fermentation on Metabolites in Lotus Leaf Based on Ultra-High-Performance Liquid Chromatography–High-Resolution Mass Spectrometry - Yubao Wang; Bingjun Lin; Zhengxu Li (Fermentation, 2022)
The lotus leaf is a raw material commonly used in slimming herbal products, but the deep processing technology is insufficient. Lactic acid bacteria (LAB) fermentation is an effective method to improve the efficacy of plant materials. In this study, ultra-high-performance liquid chromatography–high-resolution mass spectrometry (UHPLC–HR-MS) was used to explore the differential metabolites of a lotus leaf aqueous extract before and after fermentation. Information about the metabolites in the water extract of lotus leaves before and after fermentation was collected in positive- and negative-ion modes, and the metabolites identified before and after fermentation were screened by multivariate statistical analysis. A total of 91 different metabolites were obtained. They included flavonoids, alkaloids, phenylpropanoids, organic acids and derivatives, terpenoids, fatty acids and fatty acyls, phenols, amino acid derivatives and others. Compared with the metabolites’ levels before fermentation, the relative contents of 68 metabolites were upregulated after fermentation, and the relative contents of 23 metabolites were downregulated. A Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified 25 metabolic pathways, of which flavone and flavonol biosynthesis, citrate cycle and flavonoid biosynthesis were the main metabolic pathways. The results of this study can provide a basis for further research and the development of products containing lotus leaves fermented by LAB.